Workshop dan Lomba Kreativitas Pemanfaatan Daur Ulang Sampah Di Cawang Jakarta Timur - Sri Pare Eni; Galuh Widati; Sahala Simatupang; Margareta Maria Sudarwani (JURNAL ComunitÃ Servizio : Jurnal Terkait Kegiatan Pengabdian kepada Masyarakat, terkhusus bidang Teknologi, Kewirausahaan dan Sosial Kemasyarakatan, 2022)
Garbage in the capital city is one of the problems that need to be concerned. There have been many government and community programs that have sought management from management to waste cultivation from problems to blessings. In line with this movement, the Architecture Study Program, Faculty of Engineering, Christian University of Indonesia in Community Service activities invites Cawang Urban Village residents to be creative and innovate about the presence of waste in the environment so that in the future waste will not be a burden from life, but can reduce waste, utilize waste by useful creativity. This activity is expected to be able to fill the busyness, eliminate boredom but can produce useful works. Thus in the new normal era after the Covid 19 pandemic, residents of Cawang, East Jakarta can make creative and useful things by using used items in their respective homes as interior decoration elements related to the ceiling, walls and floors. The competition activity is a series of activities starting from socialization, workshops on the use of used goods for interior decoration elements. The competition was attended by representatives from each of the Neighborhood Associations (RT) of Cawang Urban Village, East Jakarta.